Accidental intralenticular injection of dexametasone intravitreal implant during the treatment of refractory diabetic macular oedema (Ukrainian Journal of Ophthalmology, 2026)
This article deals with the clinical case of accidental intralenticular injection of dexamethasone implant during the treatment of refractory diabetic macula oedema. The paper is based on a comprehensive research of similar clinical cases regarding this complication. The therapy algorithm chosen by the authors is early-surgery approach with cataract phacoemulsification and relocation of Ozurdex to the vitreous body, which showed positive clinical effect.
Keywords: diabetic retinopathy; diabetic macular oedema; dexamethasone intravitreal implant; complication; intralenticular Ozurdex implantation